PENGARUH PRODUCT, PRICE, PLACE, PROMOTION, PEOPLE & PHYSICAL EVIDENCE TERHADAP LOYALITAS PELANGGAN GRIND COFFEE - Rangga Wardana, Ilham Sucipto; Sunaryo (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2022)
At this time there are so many coffee shop businesses, the emergence of a coffee shop business that is currently rapidly bringing a new impact on lifestyle. With a new lifestyle created by the current generation, pulling coffee shop competition to a new level where the best can survive the competition. This research aims to assess and analyze the effect of product, price, place, promotion, people, and physical evidence on the loyalty of the customers of Grind Coffee in Pasuruan city. The data of this quantitative explanatory research was harvested through Likert-scaled questionnaires distributed to the coffee shop’s 85 customers meeting the criteria as re-quired by purposive sampling technique. Here validity and reliability testing were per-formed, and the analyses were conducted using multiple linear regression in SPSS for Windows version 24. This study finds that product, price, people, and physical evidence positively and significantly affect customer loyalty, while place and promotion did not have any significant effect on the loyalty.